Reducing Employment Insecurity: Further Training and the Role of the Family Context. (October 2016) - Lebert, Florence; Antal, Erika
The perception of job insecurity is known to be a stressful condition for employees. Less is known about employment insecurity and the ways employees and their families deal with it. This study investigates whether participation in further training is a strategy that employees adopt to reduce perceived employment insecurity. As participation in further training is often costly and time-consuming, we assume that the family context is of importance for the decision to take part in further training. To take account of possible self-selection, we apply a propensity score matching procedure on longitudinal data from the Swiss Household Panel (2004-2013). Three main findings can be emphasized: first, participation in further training is not a strategy adopted particularly by employees who perceive high employment insecurity as they are less likely to train than their secure counterparts. Second, even though further training is not a strategy that is actively adopted, employees who train subsequently report lower levels of perceived employment insecurity. Third, the family context indeed influences the likelihood to train: partnered employees are more likely to train and preschool-aged children act as a constraint on women's but enhance men's participation in further training. Yet, in the context of high perceived employment insecurity, children generally reduce their parents' likelihood to train as the parents may turn to other strategies that reduce perceived employment insecurity.